27-Hydroxycholesterol, an endogenous selective estrogen receptor modulator. (October 2017) - He, Sisi; Nelson, Erik R.
Highlights: 27-hydroxycholesterol (27HC) has emerged as an endogenous selective estrogen receptor modulator (SERM). Elevated cholesterol is associated with several pathological conditions. This review discusses the clinical and preclinical data for a role of 27-hydroxycholesterol in various pathological conditions. Abstract: Estrogen receptors (ERs) mediate the actions of the steroidal estrogens, and are important for the regulation of several physiological and pathophysiological processes, including reproduction, bone physiology, cardiovascular physiology and breast cancer. The unique pharmacology of the ERs allows for certain ligands, such as tamoxifen, to elicit tissue- and context-specific responses, ligands now referred to as selective estrogen receptor modulators (SERMs). Recently, the cholesterol metabolite 27-hydroxychoelsterol (27HC) has been defined as an endogenous SERM, with activities in atherosclerosis, osteoporosis, breast and prostate cancers, and neural degenerative diseases. Since 27HC concentrations closely mirror those of cholesterol, it is possible that 27HC mediates many of the biological effects of cholesterol. This paper provides an overview of ER pharmacology and summarizes the work to date implicating 27HC in various diseases. Wherever possible, we highlight clinical data in support of a role for 27HC in the diseases discussed.